Development and Feasibility of a Safety Plan Mobile Application for Adolescent Suicide Attempt Survivors. Issue 8 (August 2020) - Jeong, Yeo Won; Chang, Hye Jung; Kim, Jung A
Abstract : Past suicide attempts are a powerful predictor of suicide. This study developed and evaluated the feasibility of a mobile application for creating safety plans, which include coping strategies that can be immediately accessed and used by suicide attempt survivors during a crisis. A safety plan mobile application, called Brake of My Mind, was developed (study 1). Heuristic evaluation (for experts) and user evaluations (for health professionals and adolescent suicide attempt survivors) were performed. A pilot test was then conducted based on the theory of planned behavior to evaluate the feasibility of Brake of My Mind (study 2). Three adolescent suicide attempt survivors used a pilot version of Brake of My Mind. Attitude toward suicide attempts, subjective norms, perceived behavioral control, and suicide intentions were assessed before, immediately after, and 1 week after using Brake of My Mind. Brake of My Mind showed very few low-priority usability problems, and it was considered a "good" and "acceptable" application. In study 2, median scores for attitudes toward suicide attempts, perceived behavioral control, and suicide intentions decreased over time after using Brake of My Mind. The subjective norm scores did not change. Brake of My Mind is an acceptable application for adolescent suicide attempt survivors that appears effective in decreasing their positive attitude toward suicide attempts. Abstract : Supplemental digital content is available in the text.